FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN FOOD & BEVERAGE - VIRGINIA LISTIANI; WAHYUDI, AGUSTINUS SRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This research aims to obtain empirical evidence regarding the effect of firm size, net working capital, company efficiency, liquidity, and leverage on profitability in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during 2010–2023. is non-probability sampling of the purposive sampling category, resulting in a sample of 9 companies with 126 data. This research employs multivariate statistical techniques using multiple regression analysis on panel data. The research results indicate that net working capital has a negative effect on profitability, while company efficiency has a positive effect on profitability. Meanwhile, company size, liquidity, and leverage have no impact on profitability.